Correlation between Luminex donor‐specific crossmatches and levels of donor‐specific antibodies in pretransplantation screening. Issue 1 (29th April 2013) - Guillaume, N.; Mazouz, H.; Piot, V.; Presne, C.; Westeel, P.‐F.
Abstract: Before kidney transplantation, recipients are routinely screened for preformed antibodies and prospective crossmatches. In this study, we compared prospective Luminex donor‐specific crossmatches (LumXm) with the levels of identified, donor‐specific antibodies (DSAs). LumXm was performed for 108 patient sera, 84 of which were positive for preformed antibodies and 24 of which were negative. Although LumXm can detect class I DSAs (anti‐A and anti‐B) with a mean fluorescence intensity (MFI) as low as 2300, the assay has a 'grey zone' for MFIs up to 4000 with a sensitivity of 54% and a specificity of 100%. LumXm can detect a class II DSA (anti‐DRB1) with an MFI as low as 1300 and a sensitivity of 93% and a specificity of 99%. However, these correlations were obtained with two precautions: autocrossmatching and single‐antigen bead assay with denaturing buffer were performed in discordant cases. Moreover, LumXm failed to detect anti‐Cw and anti‐DP in the 10 cases studied. LumXm, therefore, displays certain discrepancies with respect to single‐bead assays – especially for antibodies with a low MFI. Unfortunately, LumXm has a low sensitivity for anti‐A and anti‐B class I antibodies.